Wnt10b-GSK3β-dependent Wnt/STOP signaling prevents aneuploidy in human somatic cells - Lin, Yu-Chih; Haas, Alexander; Bufe, Anja; Parbin, Sabnam; Hennecke, Magdalena; Voloshanenko, Oksana; Gross, Julia; Boutros, Michael; Acebron, Sergio P.; Bastians, Holger (Life science alliance, 2021)
Wnt signaling is crucial for proper development, tissue homeostasis and cell cycle regulation. A key role of Wnt signaling is the GSK3β-mediated stabilization of β-catenin, which mediates many of the critical roles of Wnt signaling. In addition, it was recently revealed that Wnt signaling can also act independently of β-catenin. In fact, Wnt mediated stabilization of proteins (Wnt/STOP) that involves an LRP6-DVL-dependent signaling cascade is required for proper regulation of mitosis and for faithful chromosome segregation in human somatic cells. We show that inhibition of Wnt/LRP6 signaling causes whole chromosome missegregation and aneuploidy by triggering abnormally increased microtubule growth rates in mitotic spindles, and this is mediated by increased GSK3β activity. We demonstrate that proper mitosis and maintenance of numerical chromosome stability requires continuous basal autocrine Wnt signaling that involves secretion of Wnts. Importantly, we identified Wnt10b as a Wnt ligand required for the maintenance of normal mitotic microtubule dynamics and for proper chromosome segregation. Thus, a self-maintaining Wnt10b-GSK3β-driven cellular machinery ensures the proper execution of mitosis and karyotype stability in human somatic cells.
Published online: 30 November, 2020
Gesehen am 17.02.2022